Inconsistent, insensitive translations of 'Allah' - Abd Razak, Dzulkifli (2009)
THE use of the term "Allah" has captured the attention of the media again. Of late, even a newspaper from down south carried a com mentary on the issue. The slant is usually political, and not religious, and does not throw any new light on the issue. It also does not appeal to the intellect; instead, it seems to border more on emotions that further confuse the issue. To all Muslims the term "Allah" is laden with the concept of Tauhid that Allah is "the One and Only" as defined in the Quranic language, which happens to be Arabic. Allah cannot be understood without this concept of his oneness. Any attempt to do so will amount to a vulgarism of sort, and an affront to Muslims.